ANALYSIS OF THE VARIABLES DRIVING THE E-PAYMENT INTENSITY AMONG COLLEGE STUDENTS - Wisnu Yuwono; Nurtia Sari (Journal of Business Studies and Management Review, 2021)
This study aims to analyze the influence of the variable performance expectancy, benefits, trust, self-efficacy, ease of use, and security on the use of electronic-based non-cash payment (e-payments) among students in Batam City, Riau Islands Province. The growth of e-payments in Indonesia has shown a high rate but it is still lagging behind that of several neighboring countries such as Vietnam and Thailand. Several studies on this subject have shown mixed results. By using primary data through the Smart PLS version 3.0 program tools, this study concluded that performance expectancy, benefits, self-efficacy showed a significant positive relationship with the e-payment intention, while trust, ease of use, and security showed insignificant. Based on these results, it is recommended that e-payment providers always pay attention to the needs of their users.